Perceptions of Business Actors in Kuta on Digital Payment Adoption for Enhancing Tourism Attractions in Kuta Mandalika - M. Zainul Ridho; Fuddinata, Nelyska Nisyana (Politeknik Pariwisata Lombok, 2024)
Introduction: This study examines the crucial significance of digital payments in the business environment of Kuta, a prominent tourist destination undergoing worldwide digital change. Methodology: By utilizing purposive sampling, a total of 100 respondents were specifically selected to guarantee a minimum sample size of 82 respondents for a thorough and reliable study. The research attempts to gain a full understanding of how local business actors in Kuta view and implement digital payment options using offline questionnaires. The Smart PLS SEM approach will be used to carefully analyze the obtained data to reveal insights into the perceptions and behavioral intentions associated with digital payments in these contents. Findings: The statistical significance of observed effects is assessed using p-values, which indicate the only factors that significantly and favourably influence behavioural intention (BI) to adopt digital payment systems are effort expectation (EE) and facilitating condition (FC) (p < 0.05)., the impacts of Performance Expectancy (PE) and Social Influence (SI) lack statistical significance, indicating the possibility of random outcomes. Conclusion: To summarize, the study highlights that out of the four independent variables, only Effort Expectancy and Facilitating Condition had a significant influence on behavioral intention to implement digital payment systems in Kuta. Keywords: Digital Payment, Behavioural Intention, Expectancy